Mitral valve prolapse: «Much Ado About Nothing», or a real unsolved problem? - E. V. Zemtsovsky; E. G. Malev; S. V. Reeva (Кардиоваскулярная терапия и профилактика)
The paper discusses the modern state of the mitral valve prolapse (MVP) problem. Controversial and unresolved issues on terminology, diagnostics, and tactics for different MVP variants are considered on the basis of the “Heritable disorders of connective tissue” recommendations (2009) by Expert Committee, the Society of Cardiology of the Russian Federation (VNOK). The modern diagnostic criteria of MVP are discussed, as well as echocardiography-estimated MVP prevalence while using those diagnostic criteria, and the comparison of Framingham Heart Study results to the authors’ own data. The interrelation between autonomic dysfunction and MVP is assessed, and different approaches to the stratification of MVP complication risk are compared, based on the echocardiography results and clinical data. The modern methods of MVP treatment and management strategy are also described.